2008
DOI: 10.1039/b801592a
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of 1,2-elimination reactions at the E2–E1cB interface—tert-butyl 3-tosyloxybutanoate and its thioester

Abstract: Experimental data on the stereoselectivity of base-catalyzed 1,2-elimination reactions that produce conjugated carbonyl compounds are scarce in spite of the importance of these reactions in organic and biochemistry. As part of a comprehensive study in this area, we have synthesized stereospecifically-deuterated beta-tosyloxybutanoate esters and thioesters and studied the stereoselectivity of their elimination reactions under non-ion pairing conditions. With the availability of both the (2R*,3R*) and (2R*,3S*) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 21 publications
4
28
2
Order By: Relevance
“…According to Karplus equation, vicinal coupling constants present a strong correlation with the dihedral angle (θ) enabling correlation of the 3 J CH value with E (θ = 0°) or Z (θ = 180°) stereochemistry of the double bond [25,26]. Thus, in this case, the 3 J CH = 6.9 Hz was observed in the NMR experiment, which corresponds to θ around 0°, confirming the exclusive presence of isomer E as expected, due to the most favorable anti elimination in the E1cB reaction, giving rise to a more stable E -isomer [27].…”
Section: Resultsmentioning
confidence: 53%
“…According to Karplus equation, vicinal coupling constants present a strong correlation with the dihedral angle (θ) enabling correlation of the 3 J CH value with E (θ = 0°) or Z (θ = 180°) stereochemistry of the double bond [25,26]. Thus, in this case, the 3 J CH = 6.9 Hz was observed in the NMR experiment, which corresponds to θ around 0°, confirming the exclusive presence of isomer E as expected, due to the most favorable anti elimination in the E1cB reaction, giving rise to a more stable E -isomer [27].…”
Section: Resultsmentioning
confidence: 53%
“…The (E)-alkenes were formed almost exclusively. 2,3 GC analysis of the elimination mixtures showed only 1.3% of tert-butyl (Z)-2-butenoate (9a) from 1a during the entire course of the reaction and no discernible amount of S-tert-butyl (Z)-2butenethioate (9b) from 1b. Under the reaction conditions for 1a, 29 ± 2% of 9a was shown to isomerize to 2a; thus, no more than 0.5% rearrangement could have taken place in the elimination reactions of 3a and 3b.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We already have insights into the stereoselectivity of the elimination reactions of stereospecifically deuterated tert-butyl β-trimethylacetoxyand β-tosyloxybutanoate and thiobutanoate esters for which 94−95% anti elimination occurs. 2,3 Liquid-phase density functional theory (DFT) calculations support a stepwise E1cB I pathway for these reactions, except for the elimination of TsOH from the tosyloxyester, which follows a concerted but asynchronous E2 pathway with an E1cB-like transition state. 4 It is generally recognized that anti elimination will dominate over syn elimination under normal conditions, where ion pairing or complex conformational factors of cyclic compounds do not play a major role.…”
Section: ■ Introductionmentioning
confidence: 95%
“…The stereochemistry of the 1,2-elimination reactions of tert-butyl 3-tosyloxybutanoate 55 and thioester analogue 56 (Scheme 16) have been studied by 1 H and 2 H NMR spectroscopy after stereospecific deuteration of both esters to yield single diastereomers. 39 It was observed that activation by a carbonyl group has virtually no influence on the stereoselectivity. All substrates gave 5-6% syn elimination.…”
Section: Elimination Reactionsmentioning
confidence: 99%